Release of Nitrosamines and Nitrosamine Precursors from Scrap Tires - Beita Sandí, Wilson (2021)
Materials used during manufacturing of tires can be a source of nitrosamines and/or their precursors. Here, we examined the leaching of nitrosamines and nitrosamine precursors from scrap tires under different test conditions. Tire chips of different sizes and crumb rubber were exposed to leaching solutions with pH values ranging from 4.0 to 10.0. Leachates collected from tires were analyzed for nitrosamines. Leachates were oxidized with chloramine, ozone, or ozone followed by chloramine to quantify the amount of nitrosamine precursors. While N-nitrosodimethylamine (NDMA) and N-nitrosomorpholine (NMOR) constituted more than 90% of nitrosamines, N-nitrosodibutylamine and N-nitrosopyrrolidine were also detected in the leachates. Chloramination of the leachate was found to form additional NDMA, NMOR, and other nitrosamines. While ozonation alone did not lead to formation of NDMA or NMOR, lower levels of formation of NDMA and NMOR were observed when ozonation was followed by chloramination as compared to those for only chloramination. This suggests that ozonation reduced the reactivity of nitrosamine precursors leaching from scrap tires. Furthermore, the levels of leaching of NDMA and NMOR precursors were higher under lower-pH conditions, which can be attributed to the higher solubility of protonated amines. From an environmental standpoint, these results suggest that water in contact with tire scraps (such as in urban runoff, bed media for ballast water and wastewater treatment, and ground cover for playgrounds) may potentially contain nitrosamines and nitrosamine precursors, and the amount of precursor leaching may change with the size of the tire scraps.